Measuring online services of Bangladeshi commercial banks and its impact on customer loyalty - Uddin, Md. Bashir; Haque, A. K. M. Ahasanul; Maruf, Torekol Islam (2017)
Internet banking has become one of the most popular services utilized by the Bangladeshi retail banking customers in recent years. Different bank providers are working continuously to add or improve their internet banking services in order to make their bank a better choice among their customers as well as to retain them. Despite its attractiveness, customer loyalty towards internet banking website has become an issue due to firm competition among the banks in Bangladesh. As the development and validation of a customer loyalty model in internet banking website context in Bangladesh had yet to be addressed by past studies, and model will develop in this study based on information system marketing literatures to investigate on the customer loyalty towards internet banking website.